Treatment with dasatinib or nilotinib in chronic myeloid leukemia patients who failed to respond to two previously administered tyrosine kinase inhibitors - a single center experience (Clinics, 2015)
OBJECTIVE: To evaluate hematological, cytogenetic and molecular responses as well as the overall, progression-free and event-free survivals of chronic myeloid leukemia patients treated with a third tyrosine kinase inhibitor after failing to respond to imatinib and nilotinib/dasatinib. METHODS: Bone marrow karyotyping and real-time quantitative polymerase chain reaction were performed at baseline and at 3, 6, 12 and 18 months after the initiation of treatment with a third tyrosine kinase inhibitor. Hematologic, cytogenetic and molecular responses were defined according to the European LeukemiaNet recommendations. BCR-ABL1 mutations were analyzed by Sanger sequencing. RESULTS: We evaluated 25 chronic myeloid leukemia patients who had been previously treated with imatinib and a second tyrosine kinase inhibitor. Nine patients were switched to dasatinib, and 16 patients were switched to nilotinib as a third-line therapy. Of the chronic phase patients (n=18), 89% achieved a complete hematologic response, 13% achieved a complete cytogenetic response and 24% achieved a major molecular response. The following BCR-ABL1 mutations were detected in 6/14 (43%) chronic phase patients: E255V, Y253H, M244V, F317L (2) and F359V. M351T mutation was found in one patient in the accelerated phase of the disease. The five-year overall, progression-free and event-free survivals were 86, 54 and 22% (p